Toward healthy cities: Opportunities for collaboration - Rupp, George (Springer-Verlag, 1998)
This paper locates the need for an urban health agenda in a broader social context. This broader context is characterized by increasing diversity and extensive privatization—developments that accentuate tendencies leading away from a shared sense of the common good. The paper then outlines ways that Columbia University seeks to work for healthier cities in this challenging context.